2021
DOI: 10.1177/10738584211057047
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Optical Neural Stimulation: A New Era for Personalized Medicine

Abstract: Targeted optical neural stimulation comprises infrared neural stimulation and optogenetics, which affect the nervous system through induced thermal transients and activation of light-sensitive proteins, respectively. The main advantage of this pair of optical tools is high functional selectivity, which conventional electrical stimulation lacks. Over the past 15 years, the mechanism, safety, and feasibility of optical stimulation techniques have undergone continuous investigation and development. When combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 121 publications
1
16
0
Order By: Relevance
“…Damage thresholds were analyzed based on histological hematoxylin & eosin stains, with damage reported in layers 2/3 of the cortex for exposures exceeding 0.6 J cm −2 based on in vitro and in vivo data. This study demonstrated the clinical feasibility of INS for stimulating single cortical nodes and associated sites, highlighting that millimeter selectivity is required for precise activation of neuronal networks [19].…”
Section: In-vivo Neuromodulation In Humansmentioning
confidence: 82%
See 2 more Smart Citations
“…Damage thresholds were analyzed based on histological hematoxylin & eosin stains, with damage reported in layers 2/3 of the cortex for exposures exceeding 0.6 J cm −2 based on in vitro and in vivo data. This study demonstrated the clinical feasibility of INS for stimulating single cortical nodes and associated sites, highlighting that millimeter selectivity is required for precise activation of neuronal networks [19].…”
Section: In-vivo Neuromodulation In Humansmentioning
confidence: 82%
“…The damage threshold for human spinal nerve roots was determined at 1.09 J cm −2 (λ = 2.12 µm, 10 s at f = 2 Hz, D = 550 µm) [60]. Overall, it has been suggested that the damage threshold in peripheral nerves is higher than for the cortex in rats and monkeys [19]. However, systematic optical parameter studies combined with acute and long-term thermal damage evaluation, potentially in longitudinal studies, will be important to evaluate INM for personalized medicine.…”
Section: In-vivo Neuromodulation In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…When delivered via 200 μm fiber optic in short pulse trains (0.25 ms, 200 Hz, 0.5 s), this highly focal (submillimeter) optical approach has provided a unique way of functional column-specific stimulation in primate cortex 7 . Thus, the advantages of INS over conventional electrical stimulation include high spatial selectivity, contactless delivery, and importantly for primate and human application, neuromodulation of brain sites without prior opsin expression 8,9 . Furthermore, with this precision of targeted optical fiber stimulation and MRI compatibility, focal INS combined with MRI can be used for in vivo mapping of brain networks in primates [10][11][12] and holds promise for neuromodulation in awake behaving monkeys.…”
Section: Introductionmentioning
confidence: 99%
“…When delivered via 200 μm fiber optic, this highly focal (submillimeter) optical approach has provided a unique way of functional column-specific stimulation in primate cortex [5] . Thus, advantages of INS over conventional electrical stimulation include high spatial-temporal selectivity, contactless delivery, and importantly for primate and human application, neuromodulation of brain sites without prior incorporation of opsins [6] . Furthermore, with this precision of targeted optical fiber stimulation and MRI compatibility, focal INS combined with MRI can be used for in vivo mapping of brain networks in primates [7][8] .…”
Section: Introductionmentioning
confidence: 99%